Efficacy and safety of ultrasound-guided nerve blocks in elderly surgical patients: a meta-analysis - Rong Wang; Jinlong Ju; Xiaoyi Pang (Frontiers in Medicine)
ObjectiveThis meta-analysis investigates the efficacy and safety of ultrasound-guided nerve block in geriatric surgical patients, a crucial endeavor for optimizing anesthetic protocols and enhancing perioperative medical outcomes and prognostic indices in this vulnerable patient cohort.MethodsA comprehensive literature search was conducted in major bibliographic databases, including Web of Science, PubMed, The Cochrane Library, Embase, CNKI, Wan Fang, and VIP, to identify studies investigating the utilization of ultrasound-guided nerve blocks in elderly surgical patients. The search encompassed publications from database inception to January 2025. Two independent reviewers meticulously screened the retrieved literature, extracted relevant data, and assessed the risk of bias inherent in the included studies. Subsequently, a meta-analysis was performed to synthesize the findings.ResultsTwenty-five randomized trials were included in the analysis, The meta-analysis showed that, Compared with the control group, Ultrasound-guided nerve block Blocking effective rate ([RR = 1.21 (1.11, 1.31), P < 0.001], time of onset of sensory nerve block [SMD = −2.76 (−3.67, −1.85), P < 0.001] and Duration [SMD = 2.52 (1.86, 3.18), P < 0.01]; Time to onset of motor nerve block [SMD = −1.94 (−2.68,−1.19), P < 0.001], and Duration [SMD = 1.11 (0.24, 1.98), P = 0.01] has a good effect. After the ultrasound-guided nerve block group, 4 [SMD = −1.68 (−2.68, −0.68), P < 0.001], 8 [SMD = −0.99 (−1.66, −0.32), P < 0.001], 12 [SMD = −1.03 (−1.0.48, −0.58), P < 0.001], 24 [SMD = −1.56 (−2.36, −0.75), P < 0.001] hours had all lower VAS scores than the control group. The Adverse reaction rate in the experimental group was 0.35 times that of the control group [RR = 0.35 (0.23, 0.55), P < 0.001] and no significant difference between the operating groups [SMD = 0.25 (−0.36, 0.86), P = 0.43]. Significant publication bias was found except for the duration of the motor nerve block and surgery time. Sensitivity analysis confirmed the stability of the results.ConclusionUltrasound-guided nerve blocks constitute an efficacious and safe anesthetic modality for elderly surgical patients. These findings have significant implications for the refinement of anesthetic protocols within the geriatric population, with the potential to enhance perioperative medical quality and patient outcomes. The evidence presented in this meta-analysis provides a robust foundation for the widespread adoption of ultrasound-guided nerve blocks in clinical practice for elderly surgical patients.